PEMBANGKITAN CITRA TIME EXPOSURE MENGGUNAKAN FILTER MEDIAN - Chandra Agustina, Haris; Oka Widyantara, I Made; Diafari Djuni H, I.G.A.K (Jurnal SPEKTRUM, 2021)
Time exposure (timex) image is a type of image generated from image acquisition at a certain time or image acquisition with different exposure criteria, the advantage of timex image is High Dynamic Range which can help provide details in a digital image processing. To produce a good timex image, a method is needed that is able to create a timex image from either a video or photo source. There are several methods used to produce timex images, namely Gradient-Based Synthesized, Multi-Exposure Image, and Median Filter. In this study, the three methods are compared in producing timex images with input in the form of images with over exposure and low exposure as well as video images. For testing the timex image, the Histogram, Standard Deviation, Variance, Mean, Median, and Mode parameters are used. Based on the results of research conducted on timex images with the Median Filter method, the standard deviation value is 0.0739 and the variance value is 0.0054 where this value indicates that the intensity distribution on the median timex filter image has a wider dynamic range than the other two methods. The comparison of the timex image with the fps variation shows that the higher the fps used, the better the timex image.